The Practical and Humanistic Implications of Being a Sage (shengren) in Daoism - Poškaitė, Loreta (Acta Orientalia Vilnensia, 2005)
Centre of Oriental Studies, Vilnius University The paper concentrates on the practical and humanistic aspects of the ideal of a sage (shengren) in Daoism, which reveal its paradoxicality or bi-directionality. The analysis is based of some stories from Zhuangzi, ideas from Laozi and teaching of Quanzhen school masters of the 20th century China. It is argued that the peculiarity of this ideal in Daoism stems from the idea of “mutual entailing of opposites” and the principle of reversibility (fan) as presented in Laozi and Zhuangzi and developed later into the practical view “to return into ordinary life after transcending divine life”, which is still living in the 20th century Daoism. Some reasons for its development and rebirth are indicated.